Development and Validation of a Stability-indicating HPLC Method for the Analysis of Cabazitaxel in Jevtana® Concentrate-solvent Leftover Samples - Arnamo, Hedvig; Hillebrand, Michel J.X.; Huitema, Alwin D.R.; Nuijen, Bastiaan; Rosing, Hilde; Beijnen, Jos H. (Current Pharmaceutical Analysis, 2021)
Aim/Background: In this study, a stability-indicating method of the anticancer agent cabazitaxel was developed and validated. This method will be used to determine the chemical stability of commercially available concentrate-solvent mixture cabazitaxel (Jevtana®) to examine the possibility of multi-dosing from the same product vial after storage. The impossibility to re-use leftovers today is contributing to unnecessary and significant financial waste. Methods: A forced degradation study of cabazitaxel was performed under different conditions to produce degradation products. Acidic, basic, oxidation, heat, and Ultraviolet (UV) light conditions were tested. The method to determine the stability was developed so that potential degradation products would be shown in the UV spectra after separation from cabazitaxel with a C18 column in a High- Performance Liquid Chromatography (HPLC) system. The only degradation product occurring during storage in room temperature and ambient light was identified by accurate mass Orbitrap Mass Spectrometry. Results: A stability-indicating method for cabazitaxel (Jevtana®) concentrate-solvent mixture has been developed. We demonstrated that this method can be applied to stability studies with the purpose of multi-dosing cabazitaxel from a chemical/physical stability perspective within the tested period of time and conditions. Conclusion: As an addition, the only naturally occurring degradation product found has been identified and a degradation reaction has been suggested.
Keywords: left-over